Trends in E-Commerce And Social Media Research in Asia: Five Years of Scientometric and Content Analysis - Hilmi Aulawi; Novie Susanti Suseno; Khairul Hafezad Abdullah (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
This paper aims to provide scientometric and content analysis towards e-commerce and social media research in Asia. The Web of Science (WoS) and Scopus databases were used in searching for articles. There were 884 (433 publications from the Web of Science and 451 articles from Scopus) papers analysed. Based on the analysis of two databases, the number of publications from the Web of Science database showed a significant increase yearly. In comparison, the Scopus database showed fluctuating growth every year. One of the countries that enormously contributed to the research was China, which can be seen from the author’s and country’s analyses. The ACM International Conference Proceeding Series was the most contributing conference proceedings. Based on the keyword results, there are five keywords that appear most often. Referring to the data from the last two years (2021–2022), the keywords “machine learning” and “social media marketing” are the most frequently used. These two keywords are most often associated with e-commerce and social media keywords. These findings are expected to provide a substantial understanding towards e-commerce and social media research, particularly in the Asian region. This paper will assist researchers in understanding new topics, collaborating with other researchers, and determining relevant sources and countries. Analysed keywords can inspire new research. Consequently, researchers can learn about new technology, societal changes, and impending challenges and opportunities by tracking keyword trends.